2005
DOI: 10.1149/1.1869252
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Cycling Effects on Critical Adhesion Energy and Residual Stress in Benzocyclobutene-Bonded Wafers

Abstract: The effects of thermal cycling on critical adhesion energy and residual stress at the interface between benzocyclobutene ͑BCB͒ and silicon dioxide ͑SiO 2 ͒ coated silicon wafers were evaluated by four-point bending and wafer curvature techniques. Wafers were bonded using BCB in an established ͑baseline͒ process, and the SiO 2 films were deposited by plasma-enhanced chemical vapor deposition ͑PECVD͒. Thermal cycling was done between room temperature and a peak temperature. In thermal cycling performed with 350 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…A curing temperature of 250°C requires a curing time of about 1 h. During the curing process, the BCB coating reaches a low viscous phase while cross-linking, compensating extremely well for topographic features on the wafer surfaces and achieving very strong and durable bonds. 13,60,72,192 Soft-baked and partially cured BCB coatings can be stored several days or weeks in particle-free environments before the actual wafer bonding is performed without compromising the bonding results. Substrates with diameters of up to 200 mm have been successfully bonded using BCB in combination with the presented bonding parameters.…”
Section: Adhesive Wafer Bonding With Unpatterned Adhesive Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…A curing temperature of 250°C requires a curing time of about 1 h. During the curing process, the BCB coating reaches a low viscous phase while cross-linking, compensating extremely well for topographic features on the wafer surfaces and achieving very strong and durable bonds. 13,60,72,192 Soft-baked and partially cured BCB coatings can be stored several days or weeks in particle-free environments before the actual wafer bonding is performed without compromising the bonding results. Substrates with diameters of up to 200 mm have been successfully bonded using BCB in combination with the presented bonding parameters.…”
Section: Adhesive Wafer Bonding With Unpatterned Adhesive Layersmentioning
confidence: 99%
“…Substrates with diameters of up to 200 mm have been successfully bonded using BCB in combination with the presented bonding parameters. 13,14,70,84,96,192 Figure 7 shows the bond interfaces of a 200-mm-diam bonded wafer pair in which the top wafer has been sacrificially removed to expose the BCB adhesive layer. The color fringes at the wafer surface result from small BCB thickness variations that result form BCB reflow during the wafer bonding process.…”
Section: Adhesive Wafer Bonding With Unpatterned Adhesive Layersmentioning
confidence: 99%
“…Work using BCB as a bonding layer has shown that a strong bond (adhesion energy >30 J/m 2 as measured by four-point bending) can be achieved at a bonding temperature of 250 8C; this bond remains stable at temperatures as high as 400 8C [48,50]. The mechanism for bonding in this case is proposed to be cross-linking across the original bonding interface [72,75].…”
Section: Polymer Adhesive Wafer Bondingmentioning
confidence: 92%
“…Via chains with specific contact resistance $5 Â 10 À6 O cm 2 were demonstrated [46] by integrating wafer-to-wafer alignment, bonding, HAR etching in inductively coupled plasma (ICP), HAR filling using CVD copper, and thinning to an etch stop. This approach has demonstrated that active devices and passive copper/low-k structures can survive this bonding process and an aggressive thinning process several times over [47], thermal cycling to 400 8C [48], liquid-to-liquid thermal shock, and autoclave tests [49,50], and that the advantageous stress-buffering features of BCB remain after bonding [50].…”
Section: Wafer-level 3d Using Adhesive Bondingmentioning
confidence: 99%
“…Structured silicon wafers were bonded both to unpatterned silicon wafers and Pyrex wafers. Many other papers report on the excellent properties (bonding strength, residual stress, bonding quality) of DVS-BCB bonding [34][35][36].…”
Section: Literature Reviewmentioning
confidence: 99%